Feeling Fishy When Buying from Third Parties through E-commerce Apps: An Analysis of Users' Experiences with the Apps' Interfaces - Clementino, Tiago Lucas Pereira; Moura, José Antão Beltrão (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
E-Commerce moves trillions of dollars worldwide every year, connecting buyers and sellers. However, users, increasingly attentive, view the process of paying for and receiving products and services over the Internet with suspicion, whether due to reports of negative experiences from other users or even their own. Cases of fraud are damaging to a company's image. In this article we analyze a large volume of user reviews of different marketplace-type e-commerce applications (apps) with the aim of mapping the user experience behind the interface for the transaction mediation service between buyers and sellers offered by such apps. Our results show that the impression of insecurity occurs mainly due to two elements: 1) Interface complexity - the interfaces of these applications tend to have many usability elements that may end up hindering the clarity of the process; and, 2) Communication of responsibility - when users often do not know that they are dealing with a third party or they do know, but are unaware of the limitations of the platform's mediation service. The results of the analysis carried out here demonstrate that the loss in incremental profit, when the user uninstalls the application, tends to be much greater than the losses caused directly by fraud, highlighting the need to not only provide security, but also to communicate it.